GROUNDING ISLAM MODERATION THROUGH SOCIAL MEDIA: A FORM TO PREVENT ISLAMOPHOBIA IN INDONESIA - Doli Witro; Nurul Alamin (Tatar Pasundan: Jurnal Diklat Keagamaan, 2021)
The purpose of the study is to introduce and understand the paradigm of Islamic moderation to the public through social media in terms of separating from Islamophobia. The research method is qualitative by using library research. The data analysis technique used is Critical Discourse Analysis. Misunderstanding Islam will have the potential to cause Islamophobia. Social media can be used to provide an understanding of Islamic moderation to public. Given the enormous epidemic of hoaxes on social media, media literacy education and culture of clarification must be encouraged along with grounding Islamic moderation.                                            Keywords: Islamic moderation; Islamophobia; Social Media; Literacy.